Influence of revised public health standards on health equity action: a qualitative study in Ontario, Canada - Hassen, Nadha (Int J Equity Health, 2017)
BACKGROUND: In 2008, a revised set of public health standards was released in the province of Ontario, Canada. The updated Ontario Public Health Standards (OPHS) introduced a new policy mandate that required local public health units (PHUs) to identify “priority populations” for public health programs and services. The aim of this study was to understand how this Priority Populations Mandate (PPM) facilitated or hindered action on health equity or the social determinants of health through PHUs in Ontario. METHODS: This study used two sets of qualitative data that were part of a larger study. The first set of data was 16 semi-structured key informant interviews with policymakers involved in developing the OPHS and public health practitioners. The second set of data was the qualitative component of a role-based survey sent out to all the 36 PHUs in Ontario. Thematic content analysis was conducted to iteratively develop themes to answer the research question. RESULTS: We identified six factors that both facilitated and hindered action on health equity and social determinants of health action in the province resulting from the OPHS and PPM. These six factors were grouped into three categories or themes: OPHS policy attributes (1. introducing new terminology, 2. allowing flexibility in implementation and 3. ensuring evidence-informed decision-making), health sector context into which the PPM was introduced (4. different understandings of health equity and 5. variability in existing partnerships) and implementation by PHUs (6. requirement to address the PPM). CONCLUSIONS: Although the revised OPHS and the PPM facilitated action on health equity and the social determinants of health, on the whole, this objective could have been better met. The mandate within the OPHS could have been strengthened with respect to promoting action on health equity and the social determinants of health through more clearly defined terminology, conveying a guiding health equity vision and uniting different PHU approaches to addressing health equity.